Hydrolysis of Polysaccharide Caulerpa racemosa Seaweed with Fermentation Lactobacillus plantarum SK (5) - Sudibyo, Muhammad Farid; Santoso, Joko; Desniar, Desniar (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Hydrolysis of polysaccharides can increase biological activity by changing the structure of polysaccharide functional groups and reducing molecular weight. Enzyme hydrolysis is an environmentally friendly hydrolysis method because it does not form toxic by-products. Lactobacillus plantarum can produce amylase and cellulase enzymes, which can be used to hydrolyze C. racemosa polysaccharides. This research aims to determine the best fermentation time and starter concentration in the C. racemosa polysaccharide hydrolysis process and the C. racemosa glucose concentration before and after fermentation. The research was divided into phases: phase I and II. The fermentation time in Phase I is six days, while in Phase II, it is 48 hours. The starter concentrations used are 0%, 5%, and 10%. The analysis showed that differences in starter concentration and fermentation time caused changes in the total values of LAB, TTA, pH, reducing sugar and glucose concentration. The best treatment was shown by adding 5% starter with a fermentation time of 24 hours.